2011
DOI: 10.4028/www.scientific.net/kem.465.255
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Duplex Coating on Austenitic Stainless Steel

Abstract: The aim of the article is describe duplex treatment of austenitic stainless steel X12CrNi 18 8 surface. Combination of both plasma nitriding and PVD coating by TiN/TiCN as a surface treatment has been used to improve material hardness and wear resistance without decreasing corrosion resistance. GDOES, confocal microscopy, microhardness, indentation test were applied to characterize the chemical composition, surface morphology, adhesion and hardness of duplex treated specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 3 publications
1
12
0
Order By: Relevance
“…It has been observed that a hybrid surface treatment consisting of plasma nitriding and hard coatings significantly improved the mechanical and friction-wear properties of materials, as well as the coating adhesion strength [ 16 , 17 , 18 ]. Plasma nitriding, which generates a harder barrier between the soft substrate and the hard coating [ 19 ], plays a significant role in this hybrid surface treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that a hybrid surface treatment consisting of plasma nitriding and hard coatings significantly improved the mechanical and friction-wear properties of materials, as well as the coating adhesion strength [ 16 , 17 , 18 ]. Plasma nitriding, which generates a harder barrier between the soft substrate and the hard coating [ 19 ], plays a significant role in this hybrid surface treatment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid surface treatments consisting of plasma nitriding and hard PVD coating have been proven to be successful in improving mechanical properties, wear and corrosion resistance of materials (9,10,11,12). Many studies show that, the pretreatment improved markedly the wear resistance and the stability of the coating in the wear test (9,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The issue of nitrided layers formed on austenitic steels has been intensively solved since the 1990s, when the properties of these layers such as their depth, hardness, abrasion resistance and their influence on the corrosion resistance of steels are investigated. [6][7][8][9][10]. Another possible application of such treated surfaces is as a transition layer between a soft backing material such as austenitic steels and a very hard and thin PVD coating [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%